Right ventricular function and cardiopulmonary performance among patients with heart failure supported by durable mechanical circulatory support devices - Tran, Tomio; Muralidhar, Akshay; Hunter, Kendall; Buchanan, Cullen; Coe, Greg; Hieda, Michinari; Tompkins, Christine; Zipse, Matthew; Spotts, Melanie J; Laing, Stephanie G; Fosmark, Kristina; Hoffman, Jordan; et al. (The Journal of heart and lung transplantation, 2021)
Patients with continuous-flow left ventricular assist devices (CF-LVADs) experience limitations in functional capacity and frequently, right ventricular (RV) dysfunction. We sought to characterize RV function in the context of global cardiopulmonary performance during exercise in this population. A total of 26 patients with CF-LVAD (aged 58 ± 11 years, 23 males) completed a hemodynamic assessment with either conductance catheters (Group 1, n = 13) inserted into the right ventricle to generate RV pressure‒volume loops or traditional Swan‒Ganz catheters (Group 2, n = 13) during invasive cardiopulmonary exercise testing. Hemodynamics were collected at rest, 2 sub-maximal levels of exercise, and peak effort. Breath-by-breath gas exchange parameters were collected by indirect calorimetry. Group 1 participants also completed an invasive ramp test during supine rest to determine the impact of varying levels of CF-LVAD support on RV function. In Group 1, pump speed modulations minimally influenced RV function. During upright exercise, there were modest increases in RV contractility during sub-maximal exercise, but there were no appreciable increases at peak effort. Ventricular‒arterial coupling was preserved throughout the exercise. In Group 2, there were large increases in pulmonary arterial, left-sided filling, and right-sided filling pressures during sub-maximal and peak exercises. Among all participants, the cardiac output‒oxygen uptake relationship was preserved at 5.8:1. Ventilatory efficiency was severely abnormal at 42.3 ± 11.6. Patients with CF-LVAD suffer from limited RV contractile reserve; marked elevations in pulmonary, left-sided filling, and right-sided filling pressures during exercise; and severe ventilatory inefficiency. These findings explain mechanisms for persistent reductions in functional capacity in this patient population.